The End of Marketing : Humanizing Your Brand in the Age of Social Media. - Gil, Carlos; ProQuest (firma) (London : Kogan Page, Limited, 2021)
Marketing as we know it is dead. Learn how to spend less time reaching only a limited number of followers and build more time listening to what's relevant to customers, clients and your community.
Conversational marketing -- How to tell your story and gain organic reach on TikTok -- Tapping into the TikTok community -- Your hero's journey -- Using text overlay -- Making your music count -- Following the trends -- Understanding the TikTok algorithms -- The story of Doggface -- The end of video marketing -- Conclusion -- References -- 13 Marketing in a post-pandemic society -- Lead with empathy -- Be open and honest -- Humanize your brand -- Personalize social media channels -- Finding new customers and sales opportunities -- Put in the work now to reap rewards over time -- References -- Afterword -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Marketing-Technological innovations; Internet marketing; elektronické knihy; electronic books